(untitled) (University Arena, 2025)
Optimize the training process of basketball beginners introducing preliminary training games, and show how is possible to enhance the effort capacity at the beginners basketball players. Analysis of basic issues in the selection of basketball at the stage of initiation is done poorly. Findings reported at the model level basketball training novice drivers will facilitate specific training plans for 17-24 years of age.